Pengarusutamaan Islam: Studi Atas Upaya Jamaah Jam’iyyatul Islamiyah Menangkal Isu Penyesatan dan Memperoleh Penerimaan Publik di Palembang - Herwansyah Herwansyah (Jurnal Ilmu Agama: Mengkaji Doktrin, Pemikiran, dan Fenomena Agama, 2018)
In its development, Jam'iyyatul Islamiyah was full of controversy. Despite its further development, the movement is often considered as having teachings that are not in accordance with Islamic views. Deviance of this movement can be seen from documents published by the West Sumatra High Prosecutor's Office, West Sumatra MUI and Jambi MUI. There are three reasons why Jam'iyyatul Islamiyah can survive. First, the movement chose to cooperate with the Indonesian Religious Councel (MUI) by adhering to recommendations so that its teachings were revised. Second, the movement is inclusive, and finally the movement seeks to approach the elite in its various activities is characterized by the seminars it holds.